Bioconversion From Docosahexaenoic Acid to Eicosapentaenoic Acid in the Marine Bacterium Shewanella livingstonensis Ac10 - Ogawa, Takuya; Hirose, Kazuki; Yusuf, Yustina; Kawamoto, Jun; Kurihara, Tatsuo (Frontiers in Microbiology, 2020)
Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which belong to the same class of long chain ω-3 polyunsaturated fatty acids (PUFAs), are present in marine γ-proteobacteria. In contrast to their de novo biosynthesis that has been intensively studied, their metabolic fates remain largely unknown. Detailed information regarding bacterial ω-3 PUFA metabolism would be beneficial for understanding the physiological roles of EPA/DHA as well as the industrial production of EPA, DHA, and other PUFAs. Our previous studies revealed that the EPA-producing marine bacterium Shewanella livingstonensis Ac10 produces EPA from exogenous DHA independently of de novo EPA biosynthesis, indicating the presence of an unidentified metabolic pathway that converts DHA into EPA. In this study, we attempted to reveal the molecular basis for the bioconversion through both in vivo and in vitro analyses. Mutagenesis experiments showed that the gene disruption of fadH, which encodes an auxiliary β-oxidation enzyme 2,4-dienoyl-CoA reductase, impaired EPA production under DHA-supplemented conditions, and the estimated conversion rate decreased by 86% compared to that of the parent strain. We also found that the recombinant FadH had reductase activity towards the 2,4-dienoyl-CoA derivative of DHA, whereas the intermediate did not undergo β-oxidation in the absence of the FadH protein. These results indicate that a typical β-oxidation pathway is responsible for the conversion. Furthermore, we assessed whether DHA can act as a substitute for EPA by using an EPA-less and conversion-deficient mutant. The cold-sensitive phenotype of the mutant, which is caused by the lack of EPA, was suppressed by supplementation with EPA, whereas the DHA-supplementation suppressed it to a lesser extent. Therefore, DHA can partly substitute for, but is not biologically equivalent to, EPA in S. livingstonensis Ac10.